2006
DOI: 10.1111/j.1399-6576.2006.00995.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide de‐airing in cardiac surgery

Abstract: (ENG)Background: The risks connected with the presence of air microemboli in open-heart surgery, have recently been emphasized by reports that their number is correlated with the degree of postoperative neuropsychological disorder. Insufflation of carbon dioxide (CO 2 ) into the chest wound is used in open-heart surgery to de-air the heart and great vessels. A new insufflation device, a gas-diffuser, was compared with traditional devices for de-airing in an experimental wound model. Finally, to assess the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…These observations corroborate the findings of Svenarud with gas samplings. 20 Only with the lowest flow rate (1 SLPM) or with the application of suction, does the CarbonAid max out at lower CO 2 concentrations, especially in the region of an aorta incision. The 1 SLPM flow rate in general is unusable for air emboli protection, as explained earlier, because it takes too much time to establish a steady atmosphere and the use of suction would immediately eliminate all the gas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations corroborate the findings of Svenarud with gas samplings. 20 Only with the lowest flow rate (1 SLPM) or with the application of suction, does the CarbonAid max out at lower CO 2 concentrations, especially in the region of an aorta incision. The 1 SLPM flow rate in general is unusable for air emboli protection, as explained earlier, because it takes too much time to establish a steady atmosphere and the use of suction would immediately eliminate all the gas.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,19 With the development of the first commercial CO 2 diffusor, a range of laboratory studies were performed that demonstrated that flow rate, presence of suction, and design of the diffusor make a notable difference in the remaining air content in the thorax. 20 In this article, we aim to contribute to the better understanding of CO 2 field flooding via direct visualization of the gas mixing, combined with high-speed measurements of the CO 2 concentration directly inside a thorax model.…”
Section: Perspectivementioning
confidence: 99%
“…Deairing technologies are actively investigated at present as well [ 9 , 17 , 18 ]. Carbon dioxide insufflation into wound cavity appears to be neuroprotective.…”
Section: Discussionmentioning
confidence: 99%
“…Air tends to accumulate in the highest parts of the heart including left ventricular apex, left atrial appendix, and the upper wall of the left atrium [ 9 ]. Air bubbles are mobilized into the arterial bed not only during and after the heart resumes function and CPB is stopped.…”
Section: Introductionmentioning
confidence: 99%